PERENCANAN STRATEGI DALAM UPAYA MENINGKATKAN MUTU LULUSAN DI MTS AL-WASHLIYAH KOLAM DELI SERDANG - Sahrul Tanjung; Zul Arwan; Zahiruddin Zahiruddin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2020)
This article aim to explain about the strategic planning school in MTS Al –Washliyah Kolam Deli Serdang. The method used in this research is descriptive, with the interview data collection, and documentation. The results of this study is the strategic planning that has been carried out by the head of Madrasah. The strategic planning preparation in this school starts from developing a vision and mission statement, conducting internal and external audits, set long-term goals in developing strategic plans in order to create quality graduates effectively and efficiently with strategic steps having components, first strategic steps for strengthening the human resources of teachers Mechanisms for implementing strategic plans by first improving the teachers after the students know The next step is to improve the structure of the final stage of cleanliness that will be sustainable.Keywords: Planning, Strategy, Graduates